Microwave heating of food materials: Role of susceptor. Issue 1 (April 2021) - Punathil, Lineesh; Surendran, G
Abstract: Microwave heating technique has been used to cook and process food materials due to faster heating. In this work, the effect of susceptors (secondary materials) while microwave heating of two different food materials is theoretically examined. The heating of food materials and susceptors due to the microwave power absorption has been simulated for two different food materials (beef and bread) enclosed in susceptors. Alumina and SiC are the two different susceptors considered for the study. The alumina susceptor is found to elevate the heating rate of materials with high dielectric properties (beef). While, SiC susceptor suppresses the heating rate both the materials with high and low dielectric properties (beef and bread). However, uniformity in heating of materials with low dielectric properties is increased by using SiC susceptor. The effect of susceptor thickness on average power absorption has been analyzed and maximum amount of average power is absorbed for specific sample dimensions (lies in resonating regime).